Evaluation and experience from routine use of chemiluminescence assays for serological screening of blood and plasma donations on the Alinity s system and the Alinity i system, two new fully-automated immunoassay systems in Poland - Aneta Kopacz; Dorota Kubicka-Russel; Grzegorz Liszewski; Alicja Bukowska; Sylwia Samek; Dorota Malka; Magdalena Łętowska; Piotr Grabarczyk (Practical Laboratory Medicine, 2024)
In Poland, independent evaluations under the auspices of the Institute of Hematology and Transfusion Medicine (IHTM) are mandated for any new device, assay, systems for screening samples from whole blood and plasma donors prior to implementation by Blood Transfusion Center (BTC). In last 5 years, two new systems were introduced to the market by Abbott GmbH, namely the Alinity s and the Alinity i. The evaluations performed for these two systems included the assessment of sensitivity, specificity and precision for each of the four mandatory serological screening markers in Poland: Hepatitis B Surface Antigen (HBsAg), Hepatitis C virus antibodies (Anti-HCV), HIV antibodies (anti-HIV) and Syphilis antibodies (anti-Treponema pallidum, anti-TP). Sensitivity was assessed by testing seroconversion panels, HBsAg international reference standard, well characterized local samples, and dilution panels. Specificity was assessed by testing routine donor samples. The results from Alinity i assays were compared to the results from Abbott ARCHITECT i2000SR and Ortho VITROS 3600 assays, while the results from Alinity s assays were compared to the results of ARCHITECT i2000SR assays. The evaluation of the Alinity s and Alinity i assays for sensitivity (100 %), specificity (99,92–100 %) and precision generated results that were as good as or better than generated by routinely used systems, were within acceptance criteria, and met all requirements for screening blood donor samples in accordance with Polish regulations. The specificity of the assays in routine use by BTCs, analyzed after approximately 150,000 donations on both systems, was comparable to the specificity observed during the evaluations at IHTM.